Combined Overlap Extension PCR Method for Improved Site Directed Mutagenesis - Hasnain, Hussain; Chong, Nikson Fatt Ming (Hindawi Publishing Corporation, 2016)
The combined overlap extension PCR (COE-PCR) method developed in this work combines the strengths of the overlap extension PCR (OE-PCR) method with the speed and ease of the asymmetrical overlap extension (AOE-PCR) method. This combined method allows up to 6 base pairs to be mutated at a time and requires a total of 40- 45 PCR cycles. A total of eight mutagenesis experiments were successfully carried out, with each experiment mutating between two to six base pairs. Up to four adjacent codons were changed in a single experiment. This method is especially useful for codon optimization, where doublet or triplet rare codons can be changed using a single mutagenic primer-set, in a single experiment.